Kemunduran dan Keruntuhan Daulah Bani Umawiyah di Damaskus dan Andalusia (Studi Pustaka) - Dalimunthe, Latifa Annum (Anterior Jurnal, 2018)
Year 41 H (661), began the Umayyad rule in the history of the children of political Islam in Damaskus. The development of civilization covering the fields of architecture, military organizations, trade and fiscal reforms. Then suffered a setback that eventually collapse due to, among others, (1). The weakness of the khafilah. (2). The emergence of inter-group conflict. The emergence of inter-group conflict. The direct causes of the overthrow of the emergence of new powers, spearheaded by the descendants of al-Abbas ibn Abd al-Muttalib, this movement is supported by the Bani Hashim and the Shiite group of people who feel dikelasduakan mawali by Bani Umayyad rule. On May 14, 756, Kardova successfully conquered by Abdur Rahman and his followers. In a period of more than seven centuries of Muslim rule in Andalusia (Spain) achieve glory. in the field of intellectual progress: philosophy, science, jurisprudence, music and performing arts, language and literature. Then the physical development among others in Cordova (capital of Spain), trees and flowers imported from the east, there are 491 mosques, 900 baths, establish drainage from the mountains of length 80 km) while Granada is Al-Hamra palace, palace of al-Gajar, tower Girilda. Progress achieved daulah sons Umayyad West (Andalusia), decline and eventually collapse. The deterioration factor to cause the collapse, among others: (1). Lack of clarity about the transition of power systems. (2) Economic Difficulty. (3). The absence of a unifying ideology. (4) Islamic conflict with Christianity.